Analisis Agenda Setting pada Film Kucumbu Tubuh Indahku - Ariyat Hamdan; Fajri Ahmad (Lembaga Yasin AlSys, 2026)
Although the role of film media in shaping public attention has received attention in various previous studies, research that specifically discusses the function of film as agenda setting in representing issues of body gender identity remains limited. This study aims to analyze agenda setting in the film Kucumbu Tubuh Indahku in shaping public attention and perceptions of issues of body gender identity. This study used a qualitative approach with a content analysis design, with the research object being the film Kucumbu Tubuh Indahku, which was selected through purposive sampling. Data were collected through observation and documentation, then analyzed using content analysis based on agenda-setting indicators, namely visibility, audience silence, and valence. The results showed that this film had a high level of visibility toward issues of body gender identity through the repetition of visual symbols, narrative, and the conflict of the main character. In addition, audience silence was found, marked by the dominance of the main character’s personal perspective compared with a broader social perspective. Meanwhile, the valence in the film tended to be empathetic toward the main character’s experiences. These findings contribute to the development of agenda-setting theory in the context of film media and expand understanding of the role of film as a medium that shapes public perceptions. The conclusion of this study emphasizes the importance of narrative and visual structures in shaping the media agenda, while also showing the need for filmmakers to consider the social impact of representing issues of body gender identity.